Assessment of data on vector and host competence for Japanese encephalitis virus: A systematic review update of Oliveira et al. 2018 - Dixon, Andrea L; Edache, Stephen; Oliveira, Ana R. S.; Veloso, Vanessa De Aguiar; Cernicchiaro, Natalia (My University, 2022)
Japanese Encephalitis (JE) is an emerging, zoonotic disease transmitted primarily by Culex species mosquitoes (particularly Culex tritaeniorhynchus) carrying the flavivirus Japanese encephalitis virus (JEV). Japanese encephalitis virus maintains its life cycle between mosquitoes and vertebrate hosts, primarily pigs and wading birds (Le Flohic et al., 2013). JE is an untreatable and incurable disease that, in humans, can result in inflammation of the brain (encephalitis) causing fever, headache, respiratory signs, gastrointestinal signs, confusion, seizures, coma, and, in some cases, death (Fischer et al., 2012; Kliegman et al., 2015). The United States (US) is considered a susceptible region with great potential for JEV introduction, given the availability of competent insect vectors, susceptible maintenance (avian) hosts, large populations of susceptible, amplifying hosts (domestic and feral pigs), intensive travel and trade activities to and from JEV-affected countries, and areas with similar climatic and environmental conditions to countries where the virus is epidemic. To investigate the risk of JEV introduction and establishment, Oliveira and colleagues performed a risk assessment (Oliveira et al., 2019) supported by a systematic review of vector and host competency for JEV (Oliveira et al., 2018). 3Although Oliveira et al. (2019) found the risk of introduction of JEV in the US through entry of infected mosquitoes via airplanes to be very high, the risk of establishment was considered negligible; yet, increases in international trade and globalization, as well as changes in climate and land use, and the recent incursion of a new JEV genotype into areas previously free from disease, as observed in Australia with the invasion and expansion of JEV (Genotype IV) in the eastern and southeastern states, warrants the need for an update of the review and risk assessment. The objective of this review is to update the systematic review (Oliveira et al., 2018) on host and vector competence of transmission of the Japanese encephalitis virus.